حصر أولي للأمراض الفيروسية التي تُصيب صنفي التبغ فيرجينيا Vk51 وبرلي Br21 في الساحل السوري (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
هدف البحث إلى حصر الأمراض الفيروسية على صنفي التبغ فيرجينيا Vk51 وبرلي Br21 في بعض قرى محافظتي اللاذقية (الأشرفية, العيدية, الحويز, البرجان) وطرطوس (الدكيكة, شاص) في موسم 2006-2007. تمّ مسح 36 حقلاً مزروعة بتبغ الفيرجينيا والبرلي (24 في اللاذقية, 12 في طرطوس) جُمعت خلالها 1008 عينات (504 عينات من كل صنف).  أظهرت نتائج اختبار بصمة النسيج المناعي (TBIA) عدم تفاعل أية عينة مع الأجسام المُضادة لفيروس إكس البطاطا, في حين سُجّلت فيروسات موزاييك الفصة بنسبة 0.89%, موزاييك الخيار بنسبة 33.82%, واي البطاطا بنسبة 56.74%, وموزاييك التبغ بنسبة 22.12%  في العينات المختبرة. واختلفت نسب انتشار الفيروسات في العينات باختلاف الصنف, فسُجل في عينات صنف فيرجينيا فيروسات موزاييك الفصة بنسبة 1.19%, موزاييك الخيار بنسبة 33.33%, واي البطاطا بنسبة 55.55%, وموزاييك التبغ بنسبة 23.80%, في حين سجّلت في عينات البرلي بنسب 0.59%, 34.32%, 57.93%, 20.43% على التوالي. كما اختلفت نسب انتشار الفيروسات باختلاف المناطق التي جُمعت منها العينات. ويُعد هذا البحث أول تسجيل لهذه الفيروسات على صنفي التبغ فيرجينيا Vk51 وبرلي Br21 في سورية. This search aimed to survey viral diseases of tobacco varieties Virginia Vk51 and White Burley Br21 in some villages in Lattakia (Elashrafeiah, Elaidiah, elhewaz and Elborjan) and Tartous (Eldekaikeh and Shas) provinces during 2006-2007 growing season. Thirty six tobacco fields of Virginia and White burley varieties were surveyed (Lattakia 24 fields & Tartous 12 fields), and a total of 1008 leaf samples were collected (504 samples of each variety). Results of  tissue blot immunobinding assay (TBIA) showed no positive reaction of any tested samples with PVX antibodies, and all other viruses were detected in tested samples with various ratios; AMV (0.89%), CMV (33.82%), PVY (56.74%), and TMV (22.12%). The percentage of detected viruses was varied according to tobacco varieties, and the following were recorded; AMV (1.19%), CMV (33.33%), PVY (55.55%), and TMV (23.80%) in Virginia samples, and AMV (0.59%), CMV (34.32%), PVY (57.93%), and TMV (20.43%) in White burley samples.  The percentage of detected viruses was also varied according to surveyed areas. This is the first record of viral diseases of tobacco varieties Virginia Vk51 and White Burley Br21  in Syria.